CONTRACEPTIVE CHOICE AMONG COUPLES OF CHILDBEARING AGE (PUS) IN BENGKULU PROVINCE - Henni Febriawati; Mario Ekoriano; Wulan Angraini; Edi Purwoko; Iis Suryani (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2021)
Contraceptives are very useful in achieving the family planning (keluarga berencana) program; however, not all contraceptives are suitable for everyone. The choice of contraception depends on how each person must be able to choose a contraceptive that is suitable for him or her. In general, there are two methods of contraception, namely modern and traditional. The government recommends couples of childbearing age or pasangan usia subur (PUS) to use the modern method, as it is more effective in preventing pregnancy. This study was conducted to determine factors (predisposing, enabling, and reinforcing) that influenced the use of contraceptives in Bengkulu Province. The research design was cross-sectional and used secondary data from the Performance Survey and Accountability Program/Survei Kinerja dan Akuntabilitas Program (SKAP) in 2019. The sample of this study was couples of childbearing age ranged 15-49 years old in Bengkulu. The results showed that 232 couples (59.9%) used modern contraception, while 155 people did not use modern contraception (40.1%). The results of the bivariate analysis of predisposing factors show that there is a relationship between work, education, and attitudes towards using family planning in the future, while age and knowledge are not related. It was also found that there are relationships between enabling factors such as place of residence, level of welfare, number of children, desire to have children, and informed choice. Meanwhile, there is no relationship between insurance membership and mass and room information media. It is known that there is no relationship between reinforcing factors in information sources for health workers, non-health workers, information sources for formal institutions, and information sources for non-formal institutions with the selection of contraceptive methods. The factor that most influenced the choice of family planning methods among the respondents aged 15-49 years in Bengkulu was informed choice with OR of 20.11 (95% CI = (11.24-35.98).